Fenugreek (trigonella foenum-graecum L.) seed: a review of physiological and biochemical properties and their genetic improvement (2014)
Discovering the complexity of seed structure and function along with a number of vital processes such as seed growth and development, germination are important factors in unlocking the secrets of consistent crop yield. Fenugreek (Trigonella foenum-graecum L.), a multi-purpose annual, dryland-adapted, forage, legume crop is cultivated in different parts of the world with great potential for introduction under suitable agro-climatic zones in sub-Saharan Africa and Latin America. Fenugreek seed is used extensively for its medicinal, pharmaceutical and nutraceutical properties. It is effective in the treatment of diabetes, hyperglycaemia (thyroxine-induced type) and hypercholesterolemia. This review discusses seed physiological processes and several important biochemical seed constituent, e.g., steroidal sapogenins (diosgenin), polysaccharide fiber (galactomannan), amino acid (4-hydroxyisoleucine), etc, with important medicinal and pharmacological characteristics impacting human and animal health. However, there are noticeable differences in the quality of several phytochemicals found in fenugreek seed possibly due to variations in plant genotypes and agroclimatic conditions under which the crop is grown. Hence, it is important to note that for consistent seed yield and quality of fenugreek cultivars there is an urgent need for continuing efforts in genetic improvements and in developing high yielding, disease and drought-resistant varieties suitable for different agro-climatic conditions. Therefore, in addition to the physico-biochemistry of fenugreek seed different approaches for genetic improvement have also been discussed.